The Role of Neighborhood Context in the Relationship between Parenting Effectiveness and Self-control - Stults, Brian (Crime & delinquency, 2021)
A large body of work has examined the factors contributing to low self-control among adolescents, with a predominant focus on individual and family characteristics. More recently, a small body of research has examined whether neighborhood characteristics influence self-control, with many finding null effects. We extend this research by considering whether neighborhood characteristics have a moderating influence rather than a direct effect. We examine several neighborhood characteristics, including collective efficacy, delinquency rate, and moral cynicism, as well as distinctive components of parenting effectiveness, including warmth, lack of hostility, and supervision. We find that neighborhoods do influence levels of self-control among juveniles, but primarily by helping or hindering the efforts of effective parents to instill self-control in their children.